The Giant Eruption in Solar Cycle 25 Caused by Collisional Shearing - Tao Ding; Jun Zhang; Yijun Hou (The Astrophysical Journal Letters)
On 2024 October 3, solar active region (AR) 13842 produced an X9.0 flare, which is the largest one in Solar Cycle 25 so far. Our study is to answer the question of what process caused this flare. Based on the magnetic field observations from the Solar Dynamics Observatory (SDO), we find that the nonconjugated sunspots of opposite polarities of the AR core region underwent a persistent collision process with strong shearing motions. Moreover, flux cancellation was observed at the collision region, e.g., 10 ^21 Mx of unsigned flux canceled at the local area within 2 hr, suggesting the occurrence of collisional shearing. Meanwhile, a collisional polarity inversion line (PIL) was produced in the AR core region as a result of the collision of the nonconjugated polarities during flux emergence. The SDO/Atmospheric Imaging Assembly extreme-ultraviolet observations show that two flux ropes formed above the PIL. Due to the photospheric magnetic field evolution, the two flux ropes destabilized and then erupted simultaneously. Using nonlinear force-free field modeling, we notice that there were three flux ropes at the PIL, including the two ropes mentioned above and another unobserved one. We suggest that the formation of flux ropes that carry massive accumulated free energy by the collisional shearing process and the eruption of the flux rope system are responsible for the giant flare in Solar Cycle 25.